Respuesta :

lets write the information as an equation, and name x the number unknown:
(x + 4)^2 = 36
that is:
the sum of a number and 4: (x + 4)
then, the square of the sum of a number and 4: (x + 4)^2
so we have:
(x + 4)^2 = 36
to solve we calculate square root to both sides of the equation:
(x + 4) = 6
then we solve for x:
x = 6 - 4
x = 2
so the unknown number is 2

Answer:

lets write the information as an equation, and name x the number unknown:

(x + 4)^2 = 36

that is:

the sum of a number and 4: (x + 4)

then, the square of the sum of a number and 4: (x + 4)^2

so we have:

(x + 4)^2 = 36

to solve we calculate square root to both sides of the equation:

(x + 4) = 6

then we solve for x:

x = 6 - 4

x = 2

so the unknown number is 2

Step-by-step explanation: